"Sempre di natura pigro e negligentissimo nello scrivere". Le lettere di Francesco Maria Molza (Quaderni di Gargnano, 2018)
Starting from a review of the recent publication of Francesco Maria Molza’s letters edited by Andrea Barbieri (Padova, 2014), this paper offers a reading of the Modenese poet and humanist’s remaining correspondence. The paper contemplates Molza’s approach to the epistolary genre itself and Molza’s own consciousness not only of the literary and communicative importance of his letter-writing but also of its practical limitations and the inconvenience it caused, especially because it was considered a social duty. This line of attack enables the author to reconstruct a sort of ‘counter-poetic’ of the letters writing that Molza shared with Annibal Caro. The final section comments on Molza’s thoughts in the letters he sent to his son Camillo, which make up the most part of the collection, and especially his thoughts on the idea of “fortune”.
Keywords: Italian Renaissance Literature; Letters writing; Francesco Maria Molza; Annibal Caro; Fortune